Theory and Applications on Machines, Mechanisms and Robots, and the Figure of Ettore Pennestrì - Raffaele Di Gregorio (Machines)
This editorial presents a book that marks the beginning of the MMR-T&A series, which compiles articles from the collection Machines, Mechanisms, and Robots: Theory and Applications (MMR-T&A), published in MDPI’s journal Machines [...]